1979
DOI: 10.1007/bf01235856
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic autonomic neuropathy

Abstract: This review attempts to outline the present understanding of diabetic autonomic neuropathy. The clinical features have been increasinly recognised but knowledge of the localization and morphology of the lesions and their pathogenesis remains fragmentary. A metabolic causation as postulated in somatic nerves accords best with clinical observations. Most bodily systems, particularly the cardiovascular, gastrointestinal and urogenital, are involved with added disturbances of thermoregulatory function and pupillar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
128
0
13

Year Published

1982
1982
2002
2002

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 358 publications
(142 citation statements)
references
References 208 publications
(293 reference statements)
1
128
0
13
Order By: Relevance
“…Neuropathy is a well known and common complication of DM, manifesting as sensory dominant polyneuropathies including autonomic neuropathies such as orthostatic hypotension, atonic bladder, impotence, and so forth. 1 The present study used spontaneous DM Kob rats for the detection of possible neuropathies as functions of parameters in spectral analysis of HRV or frequency domain parameters. The spontaneously diabetic BB (Bio-Breeding) Kob rat is very similar to human insulin-dependent DM patients [16][17][18][19] in terms of hypoinsulinemia, hyperglycemia, glycosuria, hyperlipidemia without obesity, depressed activity of myosin ATPase, etc.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neuropathy is a well known and common complication of DM, manifesting as sensory dominant polyneuropathies including autonomic neuropathies such as orthostatic hypotension, atonic bladder, impotence, and so forth. 1 The present study used spontaneous DM Kob rats for the detection of possible neuropathies as functions of parameters in spectral analysis of HRV or frequency domain parameters. The spontaneously diabetic BB (Bio-Breeding) Kob rat is very similar to human insulin-dependent DM patients [16][17][18][19] in terms of hypoinsulinemia, hyperglycemia, glycosuria, hyperlipidemia without obesity, depressed activity of myosin ATPase, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Thus it appears that the cardiac sympathetic nerves are less vulnerable to diabetic injury, a finding that partially confirms previous studies. 1,3,[22][23][24] Diabetic patients with autonomic neuropathy, either parasympathetic alone or combined parasympathetic and sympathetic, have an increased resting HR compared with normal subjects. 6,23 However, Bellavera et al reported that there was no significant difference in HR between healthy subjects and DM patients.…”
Section: Discussionmentioning
confidence: 99%
“…It has been commented that atony, distention and gastric emptying are generally asymptomatic because of a possible denervation of afferent sensory fibers 20 . Other authors argue that when the symptoms are present they include anorexia, nausea, vomiting and persistent fullness 1,5 .…”
Section: Discussionmentioning
confidence: 99%
“…The results suggest that STZ-induced diabetes impairs smooth muscle reactivity to nitric oxide in the rat anococcygeus muscle. [Diabetologia (1994) 37: 232-237] Key words Anococcygeus muscle (rat), diabetes, nitrergic nerves, nitric oxide, NOLA, NANC transmission, nonvascular smooth muscle, sodium nitroprusside, streptozotocin.Neuropathy of the autonomic nervous system is a complication of diabetes mellitus which may contribute to alterations in cardiovascular, gastrointestinal and genitourinary function [1,2]. These alterations may be manifested through clinical problems including postural hypotension, diabetic diarrhoea, diabetic cystopathy and impotence.…”
mentioning
confidence: 99%